2019
DOI: 10.1186/s12913-019-4400-y
|View full text |Cite
|
Sign up to set email alerts
|

The way from pen and paper to electronic documentation in a German emergency department

Abstract: Background Some of the advantages of implementing electronic emergency department information systems (EDIS) are improvements in data availability and simplification of statistical evaluations of emergency department (ED) treatments. However, for multi-center evaluations, standardized documentation is necessary. The AKTIN project (“National Emergency Department Register: Improvement of Health Services Research in Acute Medicine in Germany”) has used the “German Emergency Department Medical Record”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…7,8 Multiple studies have reported the advantages of EDIS, such as improvement of usability, 9 study recruitment, 10 visual representations, 11 and data collection. 12 Several studies have utilized artificial intelligent algorithms to automatically extract structured information from clinical notes in EMRs. 13,14 In Japan, the Next Stage ER system (NSER; TXP Medical Co. Ltd, Tokyo, Japan) has been increasingly implemented in EDs of university and tertiary care hospitals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Multiple studies have reported the advantages of EDIS, such as improvement of usability, 9 study recruitment, 10 visual representations, 11 and data collection. 12 Several studies have utilized artificial intelligent algorithms to automatically extract structured information from clinical notes in EMRs. 13,14 In Japan, the Next Stage ER system (NSER; TXP Medical Co. Ltd, Tokyo, Japan) has been increasingly implemented in EDs of university and tertiary care hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, the emergence of integrated emergency department information systems (EDISs) has changed emergency department (ED) administration and data management 7,8 . Multiple studies have reported the advantages of EDIS, such as improvement of usability, 9 study recruitment, 10 visual representations, 11 and data collection 12 . Several studies have utilized artificial intelligent algorithms to automatically extract structured information from clinical notes in EMRs 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…From a historical point of view, studies have described processes of transitioning from paper to electronic documentation in nursing and healthcare in general. [13,17,18] Implementing electronic documentation in nursing has standardized various formats of paper-based admission forms in Australia, some of which were directly automated into an electronic format. [15] From a socio-technical point of view, form content and design are often informed by working groups with physicians, nurses, clinical managers or administrators, health informaticians, and technical staff as key players.…”
Section: Discussionmentioning
confidence: 99%
“…There is an urgent need to rapidly upgrade the current paper record keeping system, which results in missing or empty files, into an electronic system. It should be obligatory to stay abreast with technological development when other medical disciplines have far advanced into this territory, even in resource limited countries (Wilson and Khansa 2018;Grange et al 2020;Katurura and Cilliers 2018;Lucas et al 2019;De Pietro and Francetic 2018;Zayyad and Toycan 2018). Nevertheless, there is a multitude of reasons why this forms a conundrum in forensic medicine just as it does in medicine (Ambinder 2005;Kalougivaki 2014).…”
Section: What Laws Currently Govern Autopsies?mentioning
confidence: 99%